Neurospecific proteins in the assessment of the condition of the spinal cord tissue under the conditions of the metabolic syndrome - Rodynsky, O.G.; Seleznyova , O.I. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. The results of the conducted research made it possible to reveal the general patterns of changes that occur after the formation of the metabolic syndrome in the nervous tissue of the spinal cord in young and old rats, which is accompanied primarily by a pathological condition, which at the cellular level was proven by changes in the indicators of neurotransmitters. Objective. The purpose of the work was to analyze the indicators of spinal cord neurotransmitters — nitrotyrosine, glutathione reductase, iNOS — inducible nitric oxide synthase and S-100 using the immunofluorescence method. Results. All indicators of these chemicals showed what changes occur in the spinal cord after the formation of metabolic syndrome. Against the background of the activity of metabolic processes in young rats, we observed an increase in the indicator of nitrotyrosine and inducible nitric oxide synthase, as an indicator of a pathological state, but against the background of intensive activity of metabolic processes, which are more pronounced in young rats, and the indicators of glutathione reductase sharply decreased in comparison with the control group. Conclusion. Thus, in our study, the indicators of neurotransmitters of spinal cord cells — nitrotyrosine, glutathione reductase, iNOS — inducible nitric oxide synthase and S-100 were analyzed using the immunofluorescence method. That is, against the background of the activity of metabolic processes in young rats, we observed an increase in the indicator of nitrotyrosine and inducible nitric oxide synthase, as an indicator of a pathological state, but against the background of intensive activity of metabolic processes, which are more pronounced in young rats, and the indicators of glutathione reductase sharply decreased in comparison with the control group, which indicated the processes of hypoxic phenomena, which were the worst in young rats, which we interpreted as the activity of the reaction at the metabolic level, and S-100, a binding protein that participates in the processes of cell growth, was increased in comparison with the control group, which we interpreted as a more pronounced pathological condition in metabolic syndrome at the cellular level.